2009
DOI: 10.1071/wf06143
|View full text |Cite
|
Sign up to set email alerts
|

Wildland surface fire spread modelling, 1990 - 2007. 1: Physical and quasi-physical models

Abstract: In recent years, advances in computational power and spatial data analysis (GIS, remote sensing, etc) have led to an increase in attempts to model the spread and behaviour of wildland fires across the landscape. This series of review papers endeavours to critically and comprehensively review all types of surface fire spread models developed since 1990. This paper reviews models of a physical or quasi-physical nature. These models are based on the fundamental chemistry and/or physics of combustion and fire spre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
217
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(249 citation statements)
references
References 101 publications
0
217
0
6
Order By: Relevance
“…In addition, interactions of fuels and weather with local topography can greatly influence fire activity (Moritz et al 2010;Sharples et al 2012). Fire behaviour models incorporate information on fuels, topography and weather to predict fire spread (Sullivan 2009a(Sullivan , 2009b(Sullivan , 2009c. Comparison of fire behaviour model outcomes against real-world fires has indicated that models typically do not accurately predict fire progression (Papadopoulos and Pavlidou 2011;Finney et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interactions of fuels and weather with local topography can greatly influence fire activity (Moritz et al 2010;Sharples et al 2012). Fire behaviour models incorporate information on fuels, topography and weather to predict fire spread (Sullivan 2009a(Sullivan , 2009b(Sullivan , 2009c. Comparison of fire behaviour model outcomes against real-world fires has indicated that models typically do not accurately predict fire progression (Papadopoulos and Pavlidou 2011;Finney et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Here we present a modeling approach that integrates information on the physics of fire spread (19)(20)(21), the effect of humans on different components of fire spread (8,22,23), and the paleoecology of modern humans (24)(25)(26). We use conceptual links between (i) known advances in human manipulation of fire, population growth, and spread and (ii) the parameters of a spatially explicit fire propagation model, to explore the types of impacts humans could have had on fire regimes as they learned to manipulate fire, their environment, and their landscapes.…”
mentioning
confidence: 99%
“…For example, the empirical tree mortality models may someday be replaced by physically based models (Butler and Dickinson 2010). Sullivan (2009aSullivan ( , 2009b) reviewed 39 models for surface fire spread developed from 1990 to 2007, and Alexander and Cruz (2012) list 20 fireline intensity-flame length relationships. Although research users may benefit from access to multiple models, fire managers will appreciate recommended models and methods.…”
Section: Future Needsmentioning
confidence: 99%